2018
DOI: 10.15547/bjvm.1082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment with enrofloxacin and Lactobacillus probiotics on ABCB1, ABCC2 and ABCG2 mRNA expression in poultry

Abstract: Poultry feed is often supplemented by Lactobacillus probiotics which may alter drug bioavailability by affecting the expression of intestinal ATP-binding cassette (ABC) efflux transporters. Therefore the effect of probiotics, administered alone or in combination with enrofloxacin, on the expression of ABCB1, ABCC2 and ABCG2 mRNAs in chickens was evaluated. Day-old Ross chicks (n=24) were divided in four equal groups. Control group was not treated. The second group received feed with addition of probiotics Lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The authors of this study observed that the drug was absorbed slower and to a lower extent in the infected birds which was related to the increased expression levels of ABCB1 mRNA, the gene encoding P-gp. Other studies carried out in poultry species found that danofloxacin and ENR treatments lead to the tendency for upregulation of ABCB1 and ABCG2 mRNA ( Haritova et al, 2008 ; Pavlova et al, 2018 ). The effect of P-gp on ENR pharmacokinetics was further proved at functional level in broilers by co-administration of verapamil, a potent and specific inhibitor of this transporter protein ( Guo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 94%
“…The authors of this study observed that the drug was absorbed slower and to a lower extent in the infected birds which was related to the increased expression levels of ABCB1 mRNA, the gene encoding P-gp. Other studies carried out in poultry species found that danofloxacin and ENR treatments lead to the tendency for upregulation of ABCB1 and ABCG2 mRNA ( Haritova et al, 2008 ; Pavlova et al, 2018 ). The effect of P-gp on ENR pharmacokinetics was further proved at functional level in broilers by co-administration of verapamil, a potent and specific inhibitor of this transporter protein ( Guo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 94%